Impact of Conservative and Operative Treatment on Functional Consequences in Patients with the Fracture of Metacarpals Bones: A Longitudinal Study - Ali Muhammad Bhutto, Hassan Amir Us Saqlain, Azizullah Bhayo, Sijad Ahmed Mahar, Rasheed Ahmed Bhatti, Nisar Ahmed Soomro, Niaz Hussain Keerio, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: The aim of this study was to compare the healing and functional outcomes of metacarpal bone fractures treated conservatively versus surgically. Study design: A longitudinal study Place and Duration: This study was conducted at Ghulam Mohammed Mahar Medical College Sukkur Pakistan. from June 2020 to June 2021 Methodology: The study comprised a total of 80 people with varied forms of metacarpal fractures. The fractures were treated conservatively or surgically in the orthopedic department. The Disabilities of the Arm, Shoulder, and Hand (DASH) questionnaire score, which was used to assess the ability to execute various tasks, inspired the creation of the questionnaire. The least level of disability was assigned a score of 0, and the most degree of disability was assigned a score of 100. Results: In the DASH questionnaire, a scale score ranging from Zero to 100 was calculated. The greater the score, the worse the scenario. The majority of the subject obtained a score of 21 to 25, suggesting that they were generally pleased with their therapy. The Michigan questionnaire was used to assess patient satisfaction as the next questionnaire. Patients' primary expectation is restoring maximum hand function, and the functional outcome is critical. Conclusion: Most metacarpal fractures have a satisfactory outcome with nonoperative therapy because there is a lot of tolerance for angulation and shortening. Physical therapy and mobilization are critical components of treating these fractures and are an important part of the rehabilitation process. More study is required to help develop a definite treatment regimen while maintaining our patients' quality of care and overall wellness.